Kanser tümörü için modellenen bir difüzyon denkleminin yaklaşık çözümleri - Demir, Özlem (Muş Alparslan Üniversitesi, 2022)
Bu çalışmada, kanser tömörü için modellenen bir difüzyon denkleminin yaklaşık çözümleri incelenmiştir. Çalışmanın temel amacı, Residual kuvvet serisi metodu (RPSM) algoritmasını kullanarak kanser tümörü için modellenen farklı problemleri çözmek ve bulunan sonuçları incelemektir. Yöntemin açıklanması ve güvenirliği göstermek için seri çözümlerin grafiksel sunumları verilmiştir. Bu yöntemin farklı kanser tümör problemlerinin yaklaşık çözümleri için alternatif olarak kullanılabileceği sonucuna varılmıştır.

In this study, approximate solutions of a diffusion equation modeled for cancer tumor were investigated. The main purpose of the study is to solve different problems modeled for cancer tumor using the Residual power series method (RPSM) algorithm and to examine the results found. Graphical representations of the serial solutions are given to explain the method and demonstrate its reliability. It has been concluded that this method can be used as an alternative for approximate solutions of different cancer tumor problems.
Numerical solutions of a diffusion equation modeled for cancer tumor
Keywords: Matematik; Mathematics